IMPROVING THE SCIENTIFIC-METHODOLOGICAL FRAMEWORK FOR ESTABLISHING A RAW MATERIAL BASE FOR INVESTMENT PROJECTS BASED ON LAND CADASTRE DATA (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the scientific and methodological foundations for integrating land cadastre data into investment processes. Based on legal, spatial, and economic indicators of cadastral information, an improved mechanism for assessing the resource base of investment objects is proposed. The results show that the completeness and accuracy of cadastral data enhance the reliability of investment decisions and contribute to reducing costs and risks.
Keywords: Land cadastre, investment processes, raw material base, geospatial information system, integrated assessment, multi-criteria analysis, quality of cadastral data, investment cost model, digital land management, integrated index.